Diagnostic et prise en charge de la dépression chez le sujet âgé [Diagnosis and management of depression in the elderly] - Tayaa, Saïd; Berrut, Gilles; Seigneurie, Anne-Sophie; Hanon, Cécile; Lestrade, Nathalie; Limosin, Frédéric; Hoertel, Nicolas (Gériatrie et psychologie neuropsychiatrie du vieillissement, 2020)
Depression in the elderly is common, and associated with major functional impact, impaired quality of life and significant risk of suicide. Often undetected, it may also be insufficiently treated when diagnosed. Few therapeutic trials have specifically addressed depression in the elderly and guidelines for screening and management are most often based on expert opinion or extrapolation of data from younger patients. The objective of this article is to provide a synthesis of current knowledge on depression in the elderly and to recall, on the one hand, the importance of a targeted screening, and, on the other hand, the importance of a personalized management resulting from a global and multidisciplinary assessment.